Equivalence in meaning: A Comparative analysis of Nida’s and Newmark’s translation theories - Al Awdi, Mohammed (Educalitra: English Education, Linguistics, and Literature Journal, 2025)
Recently, there has been an increase in studies examining equivalence in meaning in translation, particularly in relation to how translators convey complex layers of meaning. While many studies have investigated equivalence, they often emphasize literal interpretations and frequently neglecting the underlying nuances associated with these translations. This paper presents a comparative analysis of Eugene Nida’s theories of dynamic and formal equivalence and Peter Newmark’s concepts of semantic and communicative translation. These theories represent foundational approaches to achieving equivalence in translation, particularly between culturally distinct languages like English and Arabic. This study analyzes how these theories inform Nida’s dynamic equivalence prioritizes the effect on the target audience and it aiming to create a natural and culturally adapted translation, while his formal equivalence focuses on maintaining the original structure and linguistic form of the source text. In contrast, Newmark’s semantic translation strives for precise meaning, even at the cost of readability, while communicative translation emphasizes accessibility and cultural resonance. Through the applications, benefits, and limitations of each approach, this study highlights how these theories address different translation needs, from preserving textual accuracy to enhancing reader comprehension. Practical examples are provided in both Arabic and English to illustrate the distinct impacts of these theories. finally, this paper argues that the choice of translation approach depends on the specific goals and audience of the translation task, contributing insights to the ongoing discourse on effective translation strategies.